THE INFLUENCE OF ENVIRONMENT AND INTEREST TOWARD MOTIVATION OF LEARNING CIVICS - Cahya Melati; Irawan Suntoro; Yunisca Nurmalisa (FKIP Unila, 2012)
The purpose of this study is to identify and explain the influence of learning environment conditions toward motivation of learning civic Junior High School Tunas Dharma Way Galih South Lampung years lesson 2012/2013 and the influence interests of learning toward motivation of learning civic Junior High School Tunas Dharma Way Galih South Lampung years lesson 2012/2013. The method used in this research is correlational research subjects class VII Junior High School Tunas Dharma Way Galih South Lampung years lesson 2012/2013, totaling 167 students. Samples were taken for this study was 20% or 33 students. To collect data using the questionnaire technique, which is supported by interviews and documentation. Data analysis using Chi square formula. The result is a significant difference between of learning environment conditions toward motivation of learning civic class VII Junior High School Tunas Dharma Way Galih South Lampung years lesson 2012/2013.Keywords: motivation, state of the environment learning, learning interests.